Un/productive Raciality and Transnational Affiliations in Lydia Kwaâ€™s Pulse - Oâ€™Brien, Michelle (Asiatic: IIUM Journal of English Language and Literature, 2016)
This paper explores the intersections that develop as Canada and Singapore redefine the terms of their productive raciality through their respective multicultural/multiracial forms in order to remain globally competitive. It draws out these intersections as they appear in Lydia Kwaâ€™s Pulse (2010) through its engagement with the limits of â€œproductiveâ€ raciality and the desires of the sexual racial body. Set both in Singapore and Canada, Pulse explores the everyday experiences of the particular figurations that are bracketed out through the rhetoric of productive raciality in both nations â€“ including the Asianfication of Canadaâ€™s identity and Singaporeâ€™s use of â€œAsianismâ€ as part of their global multicultural identities. As Pulse considers the effects of these statesâ€™ failure to facilitate frameworks that would make ostensibly â€œunproductiveâ€ transnational figurations legible to others, it also draws out new affiliations between these bodies subjected to these effects across these distinct contexts.